Implementation of practical cases in the subject of Tutorial Action in the Degree of Primary Education at the University of Granada: A constructivist methodology - Jennifer Serrano-García; Fátima Zahra Rakdani-Arif-Billah (Advances in Building Education)
There are numerous studies in the field of education that highlight the importance of working with university students through active methodologies, in which they themselves construct their own learning. However, the reality is different. The large volume of invisible work carried out by university teaching staff, together with the importance given to research in order to assume a prestigious and stable role, as well as the lack of vocation in teaching, has led to a significant deficiency in educational quality. This has limited the implementation of innovative pedagogical practices and has negatively affected the holistic development of students. Hence the need to implement this teaching innovation, which was carried out with university students in primary education. This practice made it possible to incorporate practical and hypothetical situations into the teaching-learning process of future teachers in order to encourage their critical thinking, motivation and teamwork